Full-Thickness Retinochoroidal Incision in the Management of Central Retinal Vein Occlusion - San-Ni Chen; Ya-Chi Huang (Journal of Ophthalmology)
Purpose. To evaluate the clinical outcomes in patients with central retinal vein occlusion (CRVO) treated with full-thickness retinochoroidal incisions and to compare whether there is difference in treatment response in ischemic and nonischemic CRVO. Methods. Retrospective study of patients of CRVO receiving full-thickness retinochoroidal incisions in Changhua Christian Hospital. Fluorescein angiography (FA), slit-lamp biomicroscopy, indirect funduscopy, best corrected visual acuity, and central macular thickness (CMT) measured by optical coherence tomography were performed pre- and postoperatively. Patients were divided into an ischemic and nonischemic group according to the findings of FA. Patients were followed up for at least 1 year. Results. Twenty-eight eyes (14 ischemic and 14 nonischemic CRVO) were included. Functional retinochoroidal venous anastomosis (RCVA) was achieved in 48 of the 65 retinochoroidal incisions (73.8%). Central macular thickness (CMT) and retinal hemorrhage decreased significantly after the surgery. Significant visual gain was observed postoperatively in the nonischemic group, but not in the ischemic group. Postoperative complications included vitreous hemorrhage (17.8%), neovascular glaucoma (7.1%), and preretinal fibrovasular membrane (10.7%), all of which were in the ischemic group. Conclusions. RCVA formation induced by retinochoroidal incisions could improve venous flow, and decrease CMT and retinal hemorrhage. However, only eyes with nonischemic CRVO showed visual improvement.